Non-Occlusive Mesenteric Ischemia After Resuscitative Endovascular Balloon Occlusion of the Aorta for Out-of-Hospital Cardiac Arrest due to Massive Gastrointestinal Bleeding - Tanizaki, Shinsuke; Matsumoto, Takeo; Murasaki, Misaki; Hayashi, Minoru; Maeda, Shigenobu; Ishida, Hiroshi (Journal of Endovascular Resuscitation and Trauma Management, 2020)
Resuscitative endovascular balloon occlusion of the aorta (REBOA) has been used as a method of controlling intraabdominal bleeding in case of hemorrhagic shock and an adjunct to improve traditional advanced cardiac life support in non-traumatic cardiac arrest. Partial REBOA is proposed as an alternative method to regulate low-volume continuous blood flow across the area of occlusion with the aim of minimizing the risk of ischemia-reperfusion injury. An 82-year-old male suffered an out-of-hospital cardiac arrest due to massive gastric bleeding. He was initially resuscitated with partial REBOA but died of non-occlusive mesenteric ischemia (NOMI) or rebleeding. REBOA was performed during his cardiac arrest and deflated after the return of spontaneous circulation. We aimed for a proximal arterial pressure of 70–80 mmHg and a distal arterial pressure of 20–30 mmHg. The total time of REBOA was 25 min of complete occlusion and 88 min of partial occlusion. The possible causes of NOMI were age of the patient, the low flow state with prolonged cardiopulmonary resuscitation, the lower proximal-to-distal gradient of the partial REBOA, and the longer duration of total occlusion. Further studies may be required to determine the optimal distal pressure during partial REBOA to limit the burden of mesenteric ischemia.